Faktor – Faktor Yang Mempengaruhi Minat Mahasiswa Dalam Pemilihan Jurusan Akuntansi (Studi Kasus Pada Mahasiswa Baru Di Jurusan Akuntansi Perguruan Tinggi Kota Cimahi) - Mardiani, Rika; Lhutfi, Iqbal (Universitas Pendidikan Indonesia, 2021)
This study was conducted to find out why many students choose to continue their studies in the Accounting Department because currently in Indonesia the Accountant Profession is facing major challenges in the form of implementing several accounting standards and international auditing standards that are applied following current developments in the world. In this study, we will look at what factors affect student interest in choosing a major in Accounting, the factors to be studied are social influence, perceptions of the profession, expectations of an accountant's career with control variables, namely gender and age. The population of this study were new students in the Cimahi City College Accounting major in 2019 with 134 research respondents, the study used an explanatory research method. Data analysis using logistic regression method. The purpose of this research is to look at the characteristics of students majoring in Accounting and also the reasons behind the choice of majors which are expected to add input to the Accounting department regarding the concepts and perceptions of students at the beginning of their studies so that they can guide their students in the coming semester. Based on the results of data processing, the results of this study show that students choose to study Accounting because students have high career expectations in the Accounting Department, they especially expect high salaries and also wide job opportunities when they graduate.Â